Taxonomia e análise filogenética de Dilophus Meigen, 1803 (Diptera, Biobionidae, Bibioninae) - Prado, Daniel de Castro Schelesky (2024)
The Bibionidae family has approximately 700 extant species and more than 345 fossils. Known as “march flies” and “lovebugs”, their larvae feed on organic matter or living plant tissue, while adults can be important pollinators. The genus Dilophus Meigen is one of the most diverse within the family, with approximately 200 described species, 80 of which are found in the Neotropics, where Chile has the greatest diversity. This study aimed to fill gaps in the taxonomy and phylogeny of Dilophus, presenting redescriptions of four species, descriptions of two new species and an identification key for the Neotropical species, in addition to exploring their phylogenetic relationships using a broad sample of the taxon and other bibionids.